PENGARUH EFEKTIVITAS PENERAPAN ABSENSI FINGER PRINT TERHADAP DISIPLIN KERJA PEGAWAI NEGERI BAGIAN UMUM DAN KEPEGAWAIAN BAPPEDA PROVINSI KALIMANTAN TIMUR - Misbahul Jannah (ADMINISTRASI PUBLIK, 2018)
This study is based on the lack of discipline of employees in the general and personnel of BAPPEDA East Kalimantan Province, then the establishment of finger print absence system, in order to discipline the employees. The purpose of this study is to determine the Effectiveness Effectiveness of Fingerprint Attendance Application Against Civil Service Discipline in General and Personnel Section at Bappeda Office East Kalimantan Province.The type of research or explanation used is kuanlitatif used to analyze the influence between research variables. Types of data used are kusioner, observation, interview, and documentation.From the results of research on data analysis for the application of finger print absence based on the hypothesis calculation by using product moment correlation coefficient can be known that Ha accepted, which means there is a positive and significant relationship of 0.702 between the effectiveness of the application of finger print absence on the discipline of the General Office and staffing BAPPEDA East Kalimantan Province, and the variable effectiveness of application of finger print absence have a great influence on employee discipline, this is evident with the magnitude 81% affect the employee discipline